The Majority of United States Citizens With Cancer do not Have Access to Carbon Ion Radiotherapy - Foote, Robert L.; Tsujii, Hirohiko; Imai, Reiko; Tsuji, Hiroshi; Hug, Eugen B.; Kanai, Tatsuaki; Lu, Jiade J.; Debus, Juergen; Engenhart-Cabillic, Rita; Mahajan, Anita (Frontiers in Oncology, 2022)
As of December 31, 2020, there were 12 facilities located in Asia and Europe which were treating cancer patients with Carbon Ion Radiotherapy CIRT). Between June 1994 and December 2020, 37,548 patients were treated with CIRT worldwide. Fifteen of these patients were United States (U.S.) citizens. Using the Surveillance, Epidemiology, and End Results cancer statistics database, the Mayo Clinic in Rochester, MN has conservatively estimated that there are approximately 44,340 people diagnosed each year in the U.S. with malignancies that would benefit from treatment with CIRT. The absence of CIRT facilities in the U.S. not only limits access to CIRT for cancer care but also prevents inclusion of U.S. citizens in phase III clinical trials that will determine the comparative effectiveness and cost effectiveness of CIRT for a variety of malignancies for FDA approval and insurance coverage. Past and present phase III clinical trials have not been able to enroll U.S. citizens due to their unwillingness or inability to travel abroad for CIRT for an extended period. These barriers could be overcome with a limited number of CIRT facilities in the U.S.